Analysis of Some Heavy Metals and Organic Acids in Ficus carica Growing Adjacent in the Serpentine Soil in Sulaimani/Kurdistan, Iraq - Othman Abdulrahman Mohammed; Mohammed Rawf Hussain; Osama Hamid Shareef; Abdullah Ahmed Hama; Sardar Mohammed Weli; Fatimah Mohammed Ali; Sabiha Sharif Salih (International Journal of Food Science)
Serpentine soil refers to soil having magnesium-rich minerals such as chrysotile, lizardite, and antigorite. Fig (Ficus carica) is a plant of major importance in the world. It is a nourishing food and is used in industrial productions. This study analyzes the distribution of heavy metal contents such as nickel, cobalt, zinc, and manganese in different parts of this plant, such as its leaves, stems, and fruits. Furthermore, the organic acid content, including citric acid, fumaric acid, malic acid, and oxalic acid, was estimated. The studied area is known as Kunjirin which is a village located in the northwestern extension of the Zagros-fold-thrust belt in Mawat town, northeast of Sulaimani Province, Kurdistan Region of Iraq. The results show that there are significant differences in heavy metal contents among the plant organs except for zinc. The lowest level of heavy metals is in the fruits, while the highest amount of the heavy metal content is in the leaves. Moreover, the organic acids were unequally distributed in the plant organs. However, the lowest level of organic acids are found in the stem, while the highest concentration of the organic acids are found in the fruit part of the plant. The present study concludes that the level of heavy metals in the fruit part is within the legally admitted limits. This indicates that it is normal for human beings and animals to consume such fruits.